2018
DOI: 10.1101/480533
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutations in enterobacterial common antigen biosynthesis restore outer membrane barrier function inEscherichia coli tol-palmutants

Abstract: 23The outer membrane (OM) is an essential component of the Gram-negative bacterial cell 24 envelope that protects cells against external threats such as antibiotics. To maintain a stable and 25 functional OM barrier, cells require distinct mechanisms to ensure a balance of proteins and 26 lipids in the membrane. Crucial to this is the proper transport and assembly of various OM 27 components, of which the process of phospholipid (PL) transport is least understood. How OM 28 assembly pathways are coordinated to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 72 publications
(81 reference statements)
0
18
0
Order By: Relevance
“…In an earlier study, we have demonstrated that accumulation of intermediates in the enterobacterial common antigen (ECA) pathway is linked to restoration of OM barrier function in strains lacking Tol-Pal [26]. The fact that Tn5 insertions within wzzE were enriched in ΔtolQ and ΔtolA backgrounds (log 2 FC of +1.68 and +1.73, respectively; Fig.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In an earlier study, we have demonstrated that accumulation of intermediates in the enterobacterial common antigen (ECA) pathway is linked to restoration of OM barrier function in strains lacking Tol-Pal [26]. The fact that Tn5 insertions within wzzE were enriched in ΔtolQ and ΔtolA backgrounds (log 2 FC of +1.68 and +1.73, respectively; Fig.…”
Section: Discussionmentioning
confidence: 93%
“…A third gene involved in but not required for OPG biosynthesis, mdoD (opgD), also exhibited positive interactions with tolQ/A, albeit with lower fold-enrichment in insertion frequency (Table S4). Interestingly, we have previously found that mutations in mdoH may contribute to suppression of vancomycin sensitivity in tol-pal mutants [26]. We proceeded to validate this interaction by examining both growth and vancomycin sensitivity of a ΔtolA strain with mdoH deleted.…”
Section: Disrupting Biosynthesis Of Osmoregulated Periplasmic Glucans Results In Positive Genetic Interactions With Tol-palmentioning
confidence: 98%
See 2 more Smart Citations
“…UndPP is a shared carrier of the precursors for synthesis of O-antigen, enterobacterial common antigen (ECA), capsular polysaccharide, and peptidoglycan (101,131), and partitioning of UndPP between these pathways ensures balanced syntheses of envelope components (132)(133)(134)(135)(136). For example, mutants defective in ECA or Oantigen biogenesis demonstrate peptidoglycan defects due to accumulation of lipid-II ECA or lipid-II O-antigen , which are reversed by diverting UndPP toward peptidoglycan synthesis (132,133).…”
Section: Export Of Peptidoglycan Precursors Into the Periplasmmentioning
confidence: 99%